PREDIKSI PRODUKSI SUSU KAMBING ETAWA PADA PETERNAKAN RIDHO JAYA UNTUK MEMENUHI PERMINTAAN PASAR MENGGUNAKAN METODE SINGLE MOVING AVERAGE DAN SIMPLE LINEAR REGRESSION - muhammad al abrour; Asrianda - -; Fajriana - - (INFO-TEKNIK, 2026)
Ridho Jaya Farm is a business engaged in the production of Etawa goat milk, which experiences fluctuations in production volume over time. This condition requires an accurate prediction system to ensure that the production process can be planned more efficiently and stably. This study aims to analyze and forecast the amount of Etawa goat milk production using two forecasting methods, namely Single Moving Average (SMA) and Simple Linear Regression (SLR), as well as to compare the accuracy levels between the two. The data used in this study are daily production records collected over a certain period. Based on the analysis results, the SMA method with a period of 3 was selected because it produced forecasts closest to the actual values with a relatively stable production trend. The forecasting results show that the Etawa goat milk production volume in the next period is predicted to increase from 33 liters to around 36 liters per period, indicating a positive growth potential in production. Meanwhile, the SLR method produced a regression equation of , showing a slight downward trend in the historical data pattern. Based on the comparison of Mean Absolute Percentage Error (MAPE) values, the SMA method proved to be more accurate than the SLR method in predicting Etawa goat milk production. Therefore, the application of these forecasting methods can assist Ridho Jaya Farm in estimating future production volumes and support better decision-making in production and distribution management. Keywords: Etawa goat milk production, Forecasting, Single Moving Average (SMA), Simple Linear Regression (SLR), MAPE.